Illicit Earnings: Consequences and Approaches to Remediation - bin Naji, Hajar Abdel Wahab Ramadan; Imhaisen, Saleh Muhammad (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Illicit earnings refer to the pursuit of livelihood through unlawful means. Islam strictly prohibits such gains due to their severe consequences, which negatively impact a Muslim’s faith, acts of worship, the Islamic economy, and societal development. The remedy for illicit earnings involves returning the money to its rightful owner if known, or to their heirs if the money was unjustly taken. If the rightful owner and their heirs are unknown, the amount should be allocated to the poor and needy or used for public welfare. In cases where the original owner has died, the money should be given to their heirs, who are entitled to it; if no heirs exist, it should be donated to charitable causes.